G427(P) Retrospective audit of nutritional status assessment and management of low bone mineral density in children and young people with cerebral palsy: are we adhering to nice guidelines?. (12th March 2018) - Foong, SW; Gadde, M; Higham, D; Appleby, S; Sharma, R
Abstract : Background: Children and young people (CYP) with Cerebral Palsy (CP) are at risk of nutritional problems. Up to 90% experience difficulties in chewing or swallowing, and/or eating or drinking independently. It has been recognised that these children at risk of nutritional problems have an increased risk of bone demineralization and low-impact fractures. Feeding impairment also correlates with the severity of motor deficit (GMFCS level IV – V). Studies show that those within this category were 5.7 times more likely to have lower bone mineral density (LBMD) than GMFCS level I-III. The recent NICE guidelines have made recommendations that CYP with CP have regular reviews of their nutritional status and LBMD should be assessed and adequately managed. Aim: To ascertain (as per the NICE guidelines) a. Whether CYP with CP (GMFCS level IV–V) seen in a tertiary neurodisability service are having regular reviews of their nutritional status. b. Whether LBMD is being assessed adequately. Method: Retrospective case note analysis of CYP with CP (level IV-V) attending between March 2015- February 2017 Results: 24 children with GMFCS IV-V, CP, were identified. The male to female ratio was 11:13 96% had their weight measured 92% had their height measured 75% had a nutritional review performed 70% were referred to dieticians/for alternative methods of feeding. 62.5% of individuals had their dietary intake of vitamin D/calcium assessed at clinic 17% had investigations performed Discussion: Our findings showed that we are not achieving optimum results in mandatory areas such as measuring weight and height. Barriers identified were lack of equipment and training in mobilising a wheel chair bound child. Other areas for improvement include the need to perform regular nutritional reviews, with ongoing referrals if deemed necessary. A proforma/checklist for the service is currently being developed in order to aid clinic reviews, and a further audit will be performed in a year.